'Distributional effects of taxation in Malaysia' - F.Seling, Tenning (UiTM Sarawak, 2004)
The Faculty of Business and Management organized a talk on 'The Distributional Effects of Taxation in Malaysia' on 27 February 2004. Presented by Prof. Madya Wee Chong Hui, the one and a half hour talk focused on her carefully researched estimations of the changes in the real burden of income tax on the average Malaysian family by comparing its tax burden with the consumer price index over time.